Javanese Pitutur in the Speech of Sri Sultan Hamengku Buwono X on Hardship Caused by the Corona Virus - Doni Dwi Hartanto; Endang Nurhayati; Sulis Triyono (Ranah: Jurnal Kajian Bahasa, 2023)
Expressions of culture in a region can be seen as a discourse that represents the cultural activities of people, and it may show the nature and characters of the society in dealing with problems. This research aims to interpret the Javanese pitutur delivered by Sri Sultan Hamengku Buwono X as the King of Yogyakarta to people living in his realm during the coronavirus pandemic. This descriptive qualitative research used a recording of Sri Sultan Hamengku Buwono’s speech entitled “Cobaning Gusti Allah Awujud Virus Corona”. Data were collected through a note-checking technique and were analyzed by using content analysis. The validity was maintained through expert judgment, while the reliability was through intrarrater and interrater. The results show that Javanese pitutur or advice found in Sri Sultan Hamengku Buwono X’s speech were in four Javanese quotes, namely: a) patient people earn the greatest fortune, and surrendering their life in faith shall result in more blessings; b) God gives way to anyone who wants to obey; c) Be wise and careful; and d) Do not be jealous if you get a trial, and do not feel bad if you lose something. The Javanese pituturs as the noble expressions of Javanese culture likely represent the nature and character of Javanese society in the face of various obstacles and problems, in this case facing the COVID-19 virus pandemic in the Yogyakarta region. The messages conveyed in the pitutur are expected to be a reminder to the people of Yogyakarta that in the face of all problems they should always hold fast to their cultural values and humbly surrender and submit themselves to God the Almighty. AbstrakUngkapan budaya suatu daerah merupakan suatu wacana yang merepresentasikan aktivitas budaya masyarakat, dan menunjukkan sifat dan karakter suatu masyarakat dalam menghadapi suatu permasalahan. Penelitian ini bertujuan untuk menginterpretasikan pitutur Jawa dalam pidato Sri Sultan Hamengku Buwono X selaku Raja Yogyakarta kepada masyarakat selama masa pandemik virus corona. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan data berupa rekaman pidato Sri Sultan Hamengku Buwono X berjudul “Cobaning Gusti Allah Awujud Virus Corona”. Pengumpulan data dilakukan dengan teknik simak-catat dan dianalisis dengan menggunakan teknik analisis konten. Validitas data dilakukan dengan expert judgement, sedangkan reliabilitas yang digunakan ialah reliabilitas intra dan interrater. Berdasarkan penelitian, pitutur Jawa dalam pidato Sri Sultan Hamengku Buwono X terbagi dalam empat ungkapan, yaitu: a) wong sabar rejekine jembar, ngalah urip luwih berkah; b) Gusti paring dalan kanggo sapa wae kang gelem ndalan; c) eling lan waspada; dan d) datan serik lamun ketaman, datan susah lamun kelangan. Pitutur Jawa yang terdapat dalam ungkapan-ungkapan luhur budaya Jawa tersebut merepresentasikan sifat dan karakter masyarakat Jawa dalam menghadapi berbagai macam halangan dan permasalahan, dalam hal ini ketika menghadapi pandemik virus COVID-19 di wilayah Yogyakarta. Pesan yang disampaikan dalam pitutur tersebut diharapkan dapat menjadi pengingat bagi masyarakat Yogyakarta bahwa dalam menghadapi segala permasalahan hendaknya selalu berpegang teguh pada nilai-nilai budaya dan berserah pada Tuhan Yang Maha Kuasa.